Inclusive Education in Higher Education: Baseline Study at Universitas Negeri Malang - Ahsan Romadlon Junaidi; Dimas Arif Dewantoro; Pravisi Shanti; Gama Rahmita (Department of Special Education, 2022)
The implementation of inclusive education in higher education aims to ensure the fulfillment of the right of education for persons with disabilities. This study examined the implementation of inclusion at the Universitas Negeri Malang to obtain an illustration of the implementation of inclusive education. The three dimensions of inclusive education, including the creation of an inclusive culture, inclusive policies, and inclusive practices, become the framework for developing evaluation instruments. Respondents of this research were management staff, lecturers, education staff, and students. The creation of an inclusive culture and inclusive practice is highly rated by all stakeholders, with an average of 60. In contrast, the policy dimension deserves the greatest consideration as only students rated highly on the inclusive policy dimension. Many elements of management staff, lecturers, and education staff stated that they needed further information related to the inclusive policies.